Senile plaque calcification of the lamina circumvoluta medullaris in Alzheimer's disease. Issue 5 (20th August 2021) - Schober, Ralf; Hilbrich, Isabel; Jäger, Carsten; Holzer, Max
Abstract : Vascular calcification is a common phenomenon in the elderly, predominantly appearing in the basal ganglia and in the lamina circumvoluta medullaris of the hippocampus. Calcifications are not an inherent feature of Alzheimer's disease. On the other hand, a rare presenile type of dementia with symmetrical Fahr‐type calcifications and numerous neurofibrillary tangles without senile plaques has been described by Kosaka in 1994 and was termed "diffuse neurofibrillary tangles with calcification" (DNTC). We here report a case of Alzheimer's disease with calcifications both in the basal ganglia and in the lamina circumvoluta medullaris of the hippocampus, differing from DNTC by the presence of senile plaques. The calcifications in the hippocampus were not only vascular in nature but also covered amyloid‐β‐ and phosphorylated tau‐positive plaque‐like structures that were linearly arranged along the dentate fascia in the CA1 sector, an unusual finding of pathogenetic interest.